ENHANCING STUDENTS’ WRITING SKILL WITH PROBLEM-BASED LEARNING VIDEO IN PANDEMIC SITUATION - Ardianti, Ni Putu Eni; Nitiasih, Putu Kerti; Budiarta, Luh Gd Rahayu; Adnyayanti, Ni Luh Putu Era (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
Teaching writing still become a difficult thing for English teacher because writing has a complex process spesifically in this pandemic situation, teacher should use interesting technique to attract students’ interest. This study focused on investigating the effect of problem based learning video on students’ writing skill in pandemic situation. The population involved fourth graders in SDN 1 Banjar Bali while there were 31 fourth grade students as a sample of the study which was chosen purposively. The reseach design used a quantitative research which employed one group pretest-posttest design. The intruments consisted of instrument for treatments, writing test and writing rubric. The data collection was gathered and analysed through descriptive and inferential statistics. The results shows that the group’s pretest mean was while the posttest mean of. The pair sample test also find out that the Sig. value of Sig. (2-tailed) was .000, which was lower than the Sig. level of 0.05. It could be concluded that there is significant effect of using problem based learning video as a learning media in students’ writing skill.